Model for Predicting Borderline Mental Disorders of Law Enforcement Officers – Participants of Anti-Terrorist Operation (Law and Safety, 2019)
An analysis of the professional tasks of law enforcement officers in the context of an anti-terrorist operation suggests a significant deterioration in their psychological and physical health. Therefore, one of the relevant problems of legal psychology is the development of scientific methods for substantiating and optimizing programs for the psychological provision of the professional activities of law enforcement officers serving in such conditions (professional selection, diagnosis and support of psychological readiness, psychological support, psycho-prophylaxis, correction and rehabilitation). This is necessary to minimize the negative psychosocial consequences in the form of pronounced features of borderline mental disorders and addictive behavior with the formation of concomitant addictions to alcohol and drugs.The authors of the article have revealed the results of constructing a model for predicting borderline stress disorders of law enforcement officers. The obtained regression coefficients and the values of weighted odds ratios for each of the scales demonstrated that the variables “Dissimulation”, “Negativism”, “Distress and maladjustment”, “Indirect aggression” and “Symptom of hyperactivity” are the most significant indicators of personal qualities that predict the formation of borderline stress disorders of law enforcement officers – participants in the anti-terrorist operation; further significant are “The presence of features of post traumatic stress disorder”, “Resentment”, “Aggravation” and, finally, “Hostility”, “Physical aggression”, “Symptoms of invasion” and “Verbal aggression”.It has been substantiated that negativistic law enforcement officers with pronounced features of indirect aggressiveness to the environment, exaggerating the existing problems, with features of psychological maladjustment in the emotional sphere of personality are mostly exposed to the formation of borderline stress disorders.It is advisable to use this model for predicting borderline mental disorders during routine psycho-preventive examinations of law enforcement officers of the Ministry of Internal Affairs of Ukraine in the period between business trips to anti-terrorist operation zone.
Keywords: psychological traumatization; law enforcement officer; borderline mental disorders; stress factors; mental health; anti-terrorist operation